Implications of the Kyoto Protocol: Indonesia’s perspective - Murdiyarso, Daniel (2004)
Despite good intentions to get a solid grasp of various technical issues and put in place policy instruments related to the implementation of the Kyoto Protocol, Indonesia’s government still faces tremendous challenges in terms of disseminating information on the progress of climate treaty negotiations and gaining as wide public support as possible. This is evident in the lengthy process of ratifying the protocol. On the brink of the government’s next parliamentary sessions, the issues have yet to reach a broad audience, except for workshops, seminars, and the like that have resulted in a relatively small critical mass; hence, convincing the parliament will be another challenge. The general public perceives the Kyoto Protocol, more than anything else, as just one of the international agreements avoided by the United States’ White House. Meanwhile, government agencies have so far failed to recognize the opportunity to integrate the Clean Development Mechanism (CDM) into the national sustainable development agenda and to engage the private sector. Various studies carried out by research agencies, universities, and individual scientists clearly merit further crafting in order to promote meaningful dialogues. Experiences from the Activities Implemented Jointly (AIJ) pilot phase and other strategic studies did not sufficiently build capacity, partly because of a lack of institutional memory. Learning from a real project at a certain scale may enhance the sense of urgency and help build confidence in the Kyoto Protocol and its processes.